Analisis 'Urf terhadap Ritual Udik-Udikan dalam Pernikahan Jawa - Rahma Ririn Agustin; Farkhan Farkhan (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This research explores the 'Urf perspective on the Udik-Udikan tradition in marriage, focusing on two key questions: the practice of the Udik-Udikan tradition and its evaluation through the lens of 'Urf. The study aims to explain and analyze this tradition within an Islamic context. Conducted as field research in Krendowahono Village, Gondangrejo District, Karanganyar Regency, data were gathered through observations, interviews, and documentation. The data were then analyzed using the Miles and Huberman method, which involves data collection, reduction, presentation, and verification. The findings reveal that the Udik-Udikan tradition, where parents of the last child to marry scatter coins as a symbol of gratitude, is classified under 'Urf Fi’li (a community habit in action) and 'Urf Khās (a custom specific to a certain area and time). The tradition is deemed 'Urf Ṣhāhiḥ, meaning it is considered good and permissible within Islamic teachings, as it aligns with religious rules and emphasizes positive values.